Effects of variable temperature drying on total flavonoids, amino acids, and antioxidative characteristics along with textural properties of germinated brown rice - ZHU, Chuang; YANG, Li; WU, Yan; SUN, Xiangjun; SONG, Lihua (Food Science and Technology, 2023)
Germinated brown rice (GBR) is a kind of nutritional whole cereal food but faces an issue of long-term storage due to its high moisture content. In this study, the variable temperature (VT) drying condition for GBR was established by drying at 50°C for 60 min, followed by further drying at 70°C for 130 min. The results showed a lower percentage of fissured grains of GBR in the VT drying group (27%) than that dried at 70°C (35%) and 90°C (78%). The contents of total flavonoid, γ-aminobutyric acid (GABA), and antioxidant capacities in vitro of GBR in the VT drying group were higher than those of GBR in 90 and 110°C drying groups. The texture, color, and flavor of GBR were effectively maintained by the VT drying method compared with those of GBR dried under a higher constant temperature. This study provided reference data for the GBR drying process.